Using Box-Behnken Design for Determination of Antimony(III) in Polyethylene Terephthalate by Inductively Coupled Plasma-Optical Emission Spectroscopy - Mohd Ghazali, Nur Faten Hazira; Hanapi, Nor Suhaila Mohamad; Zaini, Nurzaimah; Anis, Ahmad Lutfi; Wan Mahmood, Wan Mohd Asyraf (Indonesian Journal of Chemistry, 2025)
Antimony (Sb), a toxic heavy metal, is widely used in plastic industries as a catalyst in producing polyethylene terephthalate (PET) due to its high catalytic efficiency and cost-effectiveness. However, its potential to leach into consumables raises significant health and environmental concerns, highlighting the need for accurate quantification methods. This study aimed to optimize microwave-assisted digestion (MW-AD) parameters for the determination of trace levels of Sb(III) in PET using inductively coupled plasma-optical emission spectroscopy (ICP-OES). A Box-Behnken Design (BBD) was employed to systematically optimize three critical factors: digestion temperature, digestion time, and sample weight. The statistical analysis confirmed the model’s reliability, with an R2 value of 0.9945, indicating a well-fitted model. The optimal conditions were determined as 200 °C digestion temperature, 15 min digestion time, and 0.1 g sample weight. Under optimal conditions, the method exhibited excellent analytical performance, achieving a limit of detection (LOD) of 1.079 mg L−1, a limit of quantification (LOQ) of 3.270 mg L−1, accuracy of 106% spike recovery, and precision with 0.81% relative standard deviation (RSD, n = 3). This validated method provides a rapid, sensitive, and efficient approach for the quantification of Sb(III) in PET samples.